King Prioritise research in new fields - Siti Nur Azwin, Zulkapri (New Straits Times, 2023)
Kuantan: Yang di-Pertuan Agong Al-Sultan Abdullah Ri'ayatuddin Al-Mustafa Billah Shah has called on Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) to prioritise research in new field such a robotics and high technology based on artificial intelligence in line with the needs of the industry.